Serum Vitamins in Adult Patients With Short Bowel Syndrome Receiving Intermittent Parenteral Nutrition - Moreno Braga, Camila Bitu; Vannucchi, Helio; Murbach Freire, Cristiana Maria [UNESP]; Marchini, Julio Sergio; Jordao Junior, Alceu Afonso; de Carvalho da Cunha, Selma Freire (Sage Publications Inc, 2011)
Background: Short bowel syndrome (SBS) occurs after massive intestinal resection, and parenteral nutrition (PN) therapy may be necessary even after a period of adaptation. The purpose of this study was to determine the vitamin status in adults with SBS receiving intermittent PN. Methods: The study was conducted on hospitalized adults with SBS who were receiving intermittent PN therapy (n = 8). Nine healthy volunteers, paired by age and sex, served as controls. Food ingestion, anthropometry, plasma folic acid, and vitamins B-12, C, A, D, E, and K were evaluated. Results: The levels of vitamins A, D, and B-12 in both groups were similar. SBS patients presented higher values of folic acid (21.3 +/- 4.4 vs 14.4 +/- 5.2, P = .01) and lower values of vitamin C (0.9 +/- 0.4 vs 1.2 +/- 0.3 mg/dL, P = .03), alpha-tocopherol (16.3 +/- 3.4 vs 24.1 +/-+/- 2.7 mu mol/L, P < .001), and phylloquinone (0.6 +/- 0.2 vs 1.0 +/- 0.5 nmol/L, P < .03). Eight-seven percent of patients had vitamin D deficiency, and all patients presented with serum vitamin E levels below reference values. Conclusions: Despite all efforts to offer all the nutrients mentioned above, SBS patients had lower serum levels of vitamins C, E, and K, similar to those observed in patients on home PN. These findings suggest that the administered vitamins were not sufficient for the intermittent PN scheme and that individual adjustments are needed depending on the patient's vitamin status. (JPEN J Parenter Enteral Nutr. 2011;35:493-498)
Keywords: nutrition evaluation; adults; parenteral nutrition; short bowel syndrome; serum vitamins